(untitled) (Geograficidade, 2024)
This article aims to discuss the actions of the Solimões river pirates in the Amazonas from the production of crime places created through their experiences and skills acquired in their lived space as caboclos and riverside people. The research area is the stretch between Tefé and Coari, the largest cities in this region. Through the bibliographic survey and interviews carried out in the field work, it is proposed to discuss the use of the territory through the excluded, the common people of the Solimões river who live the distorted social rule, where the marginals can be seen as a product of their space of life creating places with strong qualities coming from their regional identity: Amazonian placeness. This article helps to understand the marginal use of brazilian territory in the Amazon, where knowledge of traditions and of the forest represent ammunition for the action of river pirates in this part of the largest river in the world.